The Impact of NOD2 Genetic Variants on the Gut Mycobiota in Crohn's Disease Patients in Remission and in Individuals Without Gastrointestinal Inflammation. (29th October 2020) - Nelson, Andrew; Stewart, Christopher J; Kennedy, Nicholas A; Lodge, John K; Tremelling, Mark; ,; Probert, Chris S; Parkes, Miles; Mansfield, John C; Smith, Darren L; Hold, Georgina L; Lees, Charlie W; et al.
Abstract: Background and Aims: Historical and emerging data implicate fungi in Crohn's disease [CD] pathogenesis. However, a causal link between mycobiota, dysregulated immunity, and any impact of NOD2 variants remains elusive. This study aims to evaluate associations between NOD2 variants and faecal mycobiota in CD patients and non-CD subjects. Methods: Faecal samples were obtained from 34 CD patients [18 NOD2 mutant, 16 NOD2 wild-type] identified from the UK IBD Genetics Consortium. To avoid confounding influence of mucosal inflammation, CD patients were in clinical remission and had a faecal calprotectin <250 μg/g; 47 non-CD subjects were included as comparator groups, including 22 matched household [four NOD2 mutant] and 25 non-household subjects with known NOD2 genotype [14 NOD2 mutant] identified by the NIHR BioResource Cambridge. Faecal mycobiota composition was determined using internal transcribed spacer 1 [ITS1] sequencing and was compared with 16S rRNA gene sequences and volatile organic compounds. Results: CD was associated with higher numbers of fungal observed taxonomic units [OTUs] [ p = 0.033]. Principal coordinates analysis using Jaccard index [ p = 0.018] and weighted Bray‐Curtis dissimilarities [ p = 0.01] showed Candida spp. clustered closer to CD patients whereas Cryptococcus spp. clustered closer to non-CD. In CD, we found higher relative abundance of Ascomycota [ p = 0.001] and lower relative abundance Basidiomycota [ p = 0.019] phyla. An inverse relationship was found between bacterial and fungal Shannon diversity in NOD2 wild-type which was independent of CD [r = -0.349; p = 0.029]. Conclusions: This study confirms compositional changes in the gut mycobiota in CD and provides evidence that fungi may play a role in CD pathogenesis. No NOD2 genotype-specific differences were observed in the faecal mycobiota.